Delineamentos experimentais eficientes para estudos de cinética química - Ferreira, Iuri E. P.; Trinca, Luzia A. [UNESP]; Ferreira, Cláudia P. [UNESP] (Sociedade Brasileira de Química, 2014)
In this paper we show how to obtain efficient designs of experiments for fitting Michaelis-Menten and Hill equations useful in chemical studies. The search of exact D-optimal designs by using local and pseudo-Bayesian approaches is considered. Optimal designs were compared to those commonly used in practice using an efficiency measure and theoretical standard errors of the kinetic parameter estimates. In conclusion, the D-optimal designs based on the Hill equation proved efficient for estimating the parameters of both models. Furthermore, these are promising with respect to practical issues, allowing efficient estimation as well as goodness-of-fit tests and comparisons between some kinetic models.
Efficient experimental designs for chemical kinetics studies
Keywords: optimum design theory; Michaelis-Menten kinetics; Hill equation